Pengaruh Foreign Direct Invesment (FDI) Dan Pengeluaran Belanja Rumah Tangga Terhadap Pertumbuhan Ekonomi Di Nusa Tenggara Barat Tahun 2018-2023 - Natalia Gurusinga; Yani Rizal; Puty Andiny; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to see how much influence the government has on FDI and household consumption expenditure on economic growth in West Nusa Tenggara. This research uses two independent variables, namely FDI and household consumption expenditure, and one dependent variable, namely economic growth. This research uses a Six year time span from 2018-2023. The results of this study show that FDI has a positive and insignificant effect on economic growth and household consumption expenditure has a positive and significant effect on economic growth.